2019
DOI: 10.1038/s41467-019-13272-5
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond X-ray induced changes of the electronic and magnetic response of solids from electron redistribution

Abstract: Resonant X-ray absorption, where an X-ray photon excites a core electron into an unoccupied valence state, is an essential process in many standard X-ray spectroscopies. With increasing X-ray intensity, the X-ray absorption strength is expected to become nonlinear. Here, we report the onset of such a nonlinearity in the resonant X-ray absorption of magnetic Co/Pd multilayers near the Co L edge. The nonlinearity is directly observed through the change of the absorption spectrum, which is modified in less than 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 87 publications
3
38
0
Order By: Relevance
“…Likewise, for pulse durations on the order of the demagnetization time, a significant contribution of ultrafast demagnetization to the fluence dependence of scattering should be expected also at the L edges, as shown in Ref. [10].…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Likewise, for pulse durations on the order of the demagnetization time, a significant contribution of ultrafast demagnetization to the fluence dependence of scattering should be expected also at the L edges, as shown in Ref. [10].…”
mentioning
confidence: 69%
“…In line with our reasoning, this experiment has shown a stronger effect for the shorter pulse lengths, corroborating the dominantly coherent nature of the XMCD-SAS fluence dependence at the Co L 3 edge. Recently, Higley et al have shown that ultrafast demagnetization plays a nonnegligible role at the Co L 3 edge when monitoring x-ray absorption using 40 fs x-ray pulses [10]. This illustrates the competition of different mechanisms in the quenching of XMCD-based signals as a function of fluence.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, for those bnAbs that have been recovered by in vitro cultures, many have been found to be IgG1. A notable exception are antibodies targeting the MPER region, which have been isolated predominantly as IgG3 [ 154 , 155 ]. The flexibility of IgG3′s long hinge region has been suggested to favor access to the MPER epitope in very close proximity to the membrane.…”
Section: Early Prevention Of Hiv-1 Infection: Passive and Active Imentioning
confidence: 99%
“…X-ray free electron lasers (X-FELs) (Ishikawa et al, 2012) are remarkable instruments capable of producing highly coherent X-ray pulses less than 20 fs in duration. Since their inception, X-FELs have made contributions to a diverse range of disciplines spanning from condensed matter (Higley et al, 2019) and atomic molecular optics (Yang et al, 2018) to structural biology (Nogly et al, 2018) and femtosecond chemistry (Hong et al, 2015). Compared to thirdgeneration light sources, X-FELs require high-throughput data systems (Thayer et al, 2016) for writing to the disk on a per-pulse basis.…”
Section: Introductionmentioning
confidence: 99%